The Ukraine war and rising commodity prices: Implications for developing countries - Arndt, Channing; Diao, Xinshen; Dorosh, Paul A.; Pauw, Karl; Thurlow, James (Elsevier, 2023)
The Russia-Ukraine war's impact on food, fuel, and fertilizer prices is a major concern for global poverty and food insecurity. Despite numerous studies and editorials on the risks and challenges of the crisis, there is little quantitative analysis of its consequences for developing countries. We use national economywide models to measure the near-term impacts of the crisis on agrifood systems, poverty, and food insecurity in 19 countries. Despite wide variations across countries, results confirm the adverse impacts of the crisis, with a total 27.2 and 22.3 million more people pushed into poverty and hunger, respectively. Agrifood systems and poverty are more vulnerable to rising fuel and fertilizer prices, whereas hunger and diet quality are more affected by higher food prices.